Enzyme-linked immunosorbent assay for determining specific immunoglobulin M in infections caused by Leptospira interrogans serovar hardjo. - Milner, A R (1985)
An automated enzyme-linked immunosorbent assay detecting specific immunoglobulin M in infections with Leptospira interrogans serovar hardjo was evaluated on 69 patients. The test was sensitive and simple to perform, requiring a single dilution of test serum, with data expressed as units of antibody activity interpolated from a reference serum pool.